The Effect of Aqueous and Alcoholic Extracts of Punica granatum L. Pericarp on Hemolysin Production of several Bacterial species (Baghdad Science Journal, 2025)
Four local hemolysin producer bacterial isolates were selected, tow of them gram negative bacteria (Escherichia coli ,Pseudomonas aeruginosa ) and the other two were gram positive bacteria (Staphylococcus aureus , Bacillus cereus ). Minimum inhibitory concentration of the aqueous and alcoholic extracts of Punica granatum L. pericarp were determined towards the four bacterial isolates ,results obtaind showed that MICs of the aqueous extract were 200 mg/ml for E .coli and P. aeruginosa isolates while were 5 mg/ml and 2 mg/ml for B. cereus, S. aureus , respectively The MICs for the ethanolic extract were 50 mg/ml , 20 mg/ml ,1 mg/ml ,0.5 mg/ml for E. coli ,P. aeruginosa ,B. cereus ,S. aureus , respectively. The effect of Sub-MICs of the aqueous and alcoholic extracts on hemolysin production was investigated , both extracts had a suppressing effect on hemolysin production by E. coli ,P. aeruginosa ,while both extract had an inhibitory effect on hemolysin production by S. aureus and B . cereus isolates